Interspecific hybridization and crossability studies of cultivated varieties of Vigna mungo L. Hepper with Vignamungo var silvestris - V. Jayashree, A. Muthuswamy, P. Jayamani and K. K. Kumar (Electronic Journal of Plant Breeding, 2020)
Interspecific hybridization was carried out with two cultivars (CO 6 and VBN8) and one wild species Vigna mungo var. silvestris22/10 in black gram. The crossability and pollen fertility studies were conducted during investigation. Qualitative traits are recorded in the F1 generation. The hybrid from CO 6 cross had twining tendency, terminal leaflet shape, petiole colour, pod pubescence, and growth pattern similar to Vignamungo var. silvestris22/10 (male parent). The hybrid from VBN8 cross resembled the male parent for the characters viz., twining tendency and growth pattern. Hence,these qualitative traits can be used to confirm hybridity at the early stage of the crop.